Performance of Coconut Husk Activated Carbon (CHAC) for Polluted River Water Treatment - Abu Bakar Sidik, Dilaeleyana; Norman, Angel Leah; Ko Mon, Vyranath; Kuichalan, Pavitraa; Muhamad, Aida; Mohd Ismail, Nurul Izzati (Multidisciplinary Applied Research and Innovation, 2022)
In this study, the coconut husk activated carbon (CHAC) was synthesized via chemical activation and the performance in the treatment of polluted river water with palm oil mill secondary effluent (POMSE) were evaluated. CHAC was produced by carbonizing the coconut husk fibres and activation via potassium hydroxide (KOH) and dried to form CHAC. The CHAC produced was used as an adsorbent in treating polluted river water with POMSE. The best condition of initial concentration of adsobates (0-100 %) and mixing time (30-120 min) in terms of color, COD and turbidity removal were evaluated. The result indicates 50 % diluted polluted river water with POMSE using CHAC at 60 mixing time resulting higher removal of colour (78.7 %), COD (69.0 %) and turbidity (66.7 %). Thus, it can be concluded that the coconut husk activated carbon has plays an important part in the treatment of palm oil mill secondary effluent in good quality.